Texas Hold’em Anglicisms in Italian - Paola Brusasco (Revista de Lenguas para Fines Específicos, 2018)
Although gambling has a long tradition and evidence of its practice can be found even in antiquity, the game of poker – initially associated with US casinos – consolidated its present form and spread all over the world only in the 20thcentury. The late 1990s, when technology allowed poker to go online, marked the birth of a mass phenomenon attracting millions of players anywhere Internet connections were available. Interest in the game and the potential for big wins at the World Series of Poker in Las Vegas and other tournaments have resulted in the birth of communities of professionals and amateur players with their own specialised language. This paper deals with the English terms typical of the variety of poker known as Texas Hold’em which have filtered into the Italian language as direct and indirect borrowings. A small corpus of Anglicisms has been collected from Italian dictionaries and official regulations. Although only few English poker terms are registered in Italian dictionaries, their number is much higher in official regulations, where they are sometimes accompanied by Italian translation equivalents, but more often used in their original or derived forms. Such difference indicates that the influence of English in this specialised area of vocabulary is rapidly growing, with terms and phrases being assimilated as part of the jargon of poker circles and regular players.